A National Cross-sectional Study on Internet Addiction and Musculoskeletal Pain Among Jordanian Medical Students. - Alkousheh, Hazim; Shereer, Fadel Tayseer; Abu Suilik, Husam; Alkousheh, Yara; Habarneh, Abeer; Alfauri, Yara; Ismail, Waed; AlQatawneh, Rahaf; Atallah, Tala; Al-Baka'in, Sandra; Abu Al Karsaneh, Ola (Journal of Community Health, 2025)
The rise in internet use among students is a growing concern about its impact on physical health. This study aimed to assess the prevalence of internet addiction and its association with musculoskeletal pain among medical students in Jordan. A national cross-sectional study was conducted from February to March 2025 across undergraduate medical students in six Jordanian universities, using an online questionnaire that included three sections: demographics, the Internet Addiction Test (IAT), and the Nordic Musculoskeletal Questionnaire-Extended (NMQ-E). Data were analysed using descriptive statistics, chi-square tests, and multivariable logistic regression for the associations between internet addiction and musculoskeletal complaints across nine body regions. Among 1100 students, 65.9% were females. Most students fell within mild (38.7%) or moderate (27.6%) internet addiction levels, while 29.5% were classified as having normal internet use, and 4.1% showed severe addiction. Gender and academic year were not significantly associated with addiction level, though university affiliation was (p = 0.017). Musculoskeletal pain was very common, especially in the neck (67.6%), shoulders (43.5%), and lower back (38.2%). Regression analysis showed that male students had higher odds of experiencing elbow (p = 0.011) and ankle/foot pain (p = 0.049), but lower odds of neck (p < 0.001), shoulder (p < 0.001), and upper back pain (p < 0.001). Internet addiction scores showed no strong link to musculoskeletal symptoms, except for elbow discomfort (p = 0.036). Internet addiction is common among medical students in Jordan, but it shows a limited association with musculoskeletal disorders. Nonetheless, the high prevalence of both conditions highlights the need for integrated strategies that promote healthy digital habits and physical well-being among students.